The Effect of Stevia Leaves as a Sugar Substitute in Reducing the Risk of Kidney Failure: A Literature Study - Andrian Ibrahim, Riza; Lianingsih, Nestia; Cahyandari, Rini (International Journal of Health, Medicine, and Sports, 2024)
Excessive sugar consumption has been linked to an increased risk of kidney failure, prompting research into alternative sweeteners. This literature study investigates the potential of Stevia leaves (Stevia rebaudiana) as a sugar substitute in reducing the risk of kidney failure. A comprehensive review of studies published between 2013 and 2023 was conducted using databases such as PubMed, ScienceDirect, and Google Scholar. The analysis revealed that high sugar intake, particularly from sweetened beverages, is associated with a higher risk of chronic kidney disease (CKD). Stevia, a zero-calorie sweetener, demonstrated promising results in weight management and glycemic control, both crucial factors in kidney health. Several studies reported improvements in kidney function markers, including serum creatinine and microalbumin levels, in CKD patients supplemented with Stevia. Additionally, Stevia's antioxidant properties may protect kidney tissues from oxidative stress. While the findings suggest Stevia's potential as a beneficial sugar substitute for kidney health, limitations in current research, including short study durations and unclear mechanisms of action, highlight the need for more comprehensive, long-term studies. This review concludes that Stevia shows promise as a tool in the prevention and management of kidney diseases, but further research is needed to fully understand its role and optimize its use in dietary interventions for kidney health.